2001
DOI: 10.3233/jad-2001-3203
|View full text |Cite
|
Sign up to set email alerts
|

PAMP and PARL, two novel putative metalloproteases interacting with the COOH-terminus of Presenilin-1 and -2

Abstract: The familial Alzheimer's disease gene products, presenilin-1 and presenilin-2 (PS1 and PS2), are involved in amyloid β-protein precursor processing (AβPP), Notch receptor signaling, and programmed cell death. However, the molecular mechanisms by which presenilins regulate these processes remain unknown. Clues about the function of a protein can be obtained by seeing whether it interacts with another protein of known function. Using the yeast two-hybrid system, we identified two proteins that interact and coloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Another stress-related transcript upregulated during migration codes for a rhomboid protease of the inner mitochondrial membrane, presenilin-associated rhomboid protease (PARL), originally named for its interaction with presenilin and its role in the processing of amyloid beta precursor protein (Pellegrini et al 2001). Recent data, however, indicates that PARL plays an important regulatory role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another stress-related transcript upregulated during migration codes for a rhomboid protease of the inner mitochondrial membrane, presenilin-associated rhomboid protease (PARL), originally named for its interaction with presenilin and its role in the processing of amyloid beta precursor protein (Pellegrini et al 2001). Recent data, however, indicates that PARL plays an important regulatory role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…25 This suggested the possibility that Opa1, like its yeast orthologue Mgm1p, undergoes posttranscriptional modification leading to its proteolytic cleavage and to the production of this shorter IMS form by Rbd1p, a rhomboid protease [63][64][65] whose orthologue in mammals is called Parl. 8 Rhomboids are a widely conserved polytopic-membraneprotein family. 66 In D. melanogaster they activate the epidermal growth factor (EGF) signalling pathway, by proteolytically cleaving the EGF receptor ligands Spitz, Gurken and Keren.…”
Section: Opa1 and The Cristae Remodelling Pathway In Apoptosismentioning
confidence: 99%
“…Members of the Parl subfamily, prototyped by Parl itself, have an extra TMH N terminus to the 6-TMH catalytic core, a '1 þ 6' structure. 8 These additional TMHs imply the existence of a loop connecting them to the 6-TMH catalytic core. The functional role of this domain remains unknown.…”
Section: Opa1 and The Cristae Remodelling Pathway In Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…PARL, presenilin-associated rhomboid-like, derives its name from being identified in a yeast two-hybrid screen for proteins that could interact with Alzheimer's presenilin protein (Pellegrini et al 2001), although this association does not occur physiologically. The first functions of a PARL protease were discovered in the budding yeast: early genome-wide screens revealed that its homolog of PARL, Pcp1 (also called Rbd1 and Ygr101w), is localized to mitochondria (Steinmetz et al 2002), and its deletion results in mitochondrial fragmentation (Dimmer et al 2002), but the basis was unclear.…”
Section: Rhomboid Proteins In Human Diseasementioning
confidence: 99%